2003
DOI: 10.1046/j.1442-2042.2003.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Device to promote pelvic floor muscle training for stress incontinence

Abstract: Aim : Many patients with stress urinary incontinence do not have enough motivation to continue pelvic floor muscle training (PFMT) by themselves. Therefore, a device was created to support PFMT, and its effect was examined. Methods : Forty-six women with stress urinary incontinence were assigned to a control group or a device group in order of presentation. A pamphlet on PFMT was given to control patients, while the same pamphlet plus the device and instructions on its use were given to patients in the device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
0
23
1
2
Order By: Relevance
“…This was a better result than what was obtained by Sugaya et al, 18 who did not observe any signifi cant effect.…”
Section: Referencescontrasting
confidence: 55%
See 1 more Smart Citation
“…This was a better result than what was obtained by Sugaya et al, 18 who did not observe any signifi cant effect.…”
Section: Referencescontrasting
confidence: 55%
“…More recently, Sugaya et al 18 compared the effi cacy of an electronic device used in perineal exercises at home, for two months. In that study, 41 patients were randomly placed into two groups: one that performed exercises for two minutes every time a device sounded (three times a day), and another, the control group (n = 20) wich was instructed to perform the same amount of exercises.…”
mentioning
confidence: 99%
“…Standard management of patients with stress incontinence includes guidance about pelvic floor exercises and keeping a voiding diary, but most patients find it difficult to persist with such measures. We previously carried out a study on the effect of an alarm device . We found that the device group was better motivated to carry out pelvic floor exercises because the alarm reminded them to do so, and the response to exercise was significantly greater in the device group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two trials have investigated the use of adherence strategies as a means of rendering PFM training more effective in women with SUI. In both trials, two groups followed the same daily home‐based PFM training programme, but one was provided with an adherence strategy 30, 31. In the Sugaya study, participants were provided with a device emitting a rhythmic beep, signaling them to undertake a contraction; they also pressed a button on the device to record each contraction 30.…”
Section: Types Of Behavior and Adherence Strategies For Effective Pfmmentioning
confidence: 99%